Curatorship and narratives: telling stories of Brazilianness and cultures through exhibitions - Bastos, Sandra Regina (Revista do Colóquio, 2025)
The research aims to examine the construction of meanings in exhibitions based on contemporary approaches to curatorship, anchored in the references of Hans Ulrich Obrist (2015), who understands the curator as a mediating agent, and Nicolas Bourriaud (2009), whose emphasis is on relational aesthetics. Based on the analysis of different curatorial practices, different modes of narrative production are observed, which adapt to the specific contexts in which they are inserted, whether museological or based on experiences in exhibition environments. In this context, the notion of Brazilianness represents an articulating component between work, territory and cultural memory. The study also explores the intersections between tradition and contemporaneity, incorporating multiple temporalities between erudite and popular, configuring itself as a structuring element in the constitution of cultural identities and in the production of meaning in the artistic field. The role of digital technologies as catalysts for innovation in curatorial processes and artistic practices stands out.
Keywords: curation; narratives; exhibitions; art; Brazilian identity.